Urgensi Pemisahan Penyelenggaraan Pemilihan Umum Serentak Nasional dan Lokal - Sirajuddin Sirajuddin; Febriansyah Ramadhan; Ilham Dwi Rafiqi (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This paper aims to evaluate the simultaneous elections and view the legal politics of separating the implementation of the simultaneous national and local elections for strengthening democracy in Indonesia. This study uses a normative juridical research method with a statutory and conceptual approaches. The results of the study show that the implementation of simultaneous elections in 2019 provided problems for organizers and voters. One of the suggestions for reforming the elections is to separate local and national elections. The the legal politics objectives of separating the elections consist of two, namely the level of organizers and voters as well as aspects of the election process and the quality of election results. This separation is expected to remove voter pragmatism, and focus more on the vision and mission of the candidates. Political parties will also carry out their functions optimally, be focused, and be able to carry out political education as they should.